Tibia malunion with angular deformity: Corrective osteotomy and intramedullary fixation with the chipping technique - Mohd Yusof, Nazri; Abot, Muhammad Syukree (Biomedical Research Network+, LLC, 2018)
There are few options for correcting severe malunion of tibial shaft. Acute correction by close wedge osteotomy followed by fixation with plate is a standard treatment for this but associated with shortening and non-union. Gradual correction with circular external fixation is able to correct the deformity without producing shortening. However it is uncomfortable and require tedious nursing and rehabilitative care. Chipping the non-union site was associated with a favorable outcome for femur fracture because it biologically enhances fracture healing. However, there is no report on chipping osteotomy for tibia mal-union. We consider chipping osteotomy as a treatment option for this patient who refuses to have external fixation for his treatment. Patient achieved corrected alignment of tibia and fracture union in 5 months. However he develops problem with wound healing of the wound.